Effects of aquatic exercise on arterial stiffness and endothelial function in adults: A systematic review and meta-analyses - Emily Dunlap; Yanbing Zhou; Manny M.Y. Kwok; Billy C.L. So; Hirofumi Tanaka (PLoS ONE, 2025)
Objective To evaluate the effects of aquatic exercise compared with non-exercise controls and land-based exercise on arterial stiffness and endothelial function. Design Systematic review and meta-analyses of randomized controlled trials assessed using the Cochrane risk-of-bias tool and Grading of Recommendations Assessment, Development and Evaluation. Data sources PubMed/MEDLINE, CINAHL Plus, SPORTDiscus, and reference lists, searched from database inception to April 16, 2025. Eligibility criteria Studies evaluating chronic aquatic exercise (multi-session interventions) compared with land-based exercise or non-exercise comparison groups in adults, measuring arterial stiffness via pulse wave velocity (PWV) or endothelial function via flow-mediated dilation (FMD). Results This review includes 18 randomized controlled trials with 845 participants (mean age 65 ± 7 years). Studies compared aquatic exercise with non-exercise controls (8 studies), land-based exercise (6 studies), or both (4 studies). Exercise sessions averaged 50 minutes, 3 times weekly for 11 weeks. Most studies (17 out of 18) implemented moderate-to-vigorous intensity protocols. Aquatic exercise resulted in improvements in arterial stiffness compared with non-exercise controls (7 studies; SMD = –2.37, 95% CI: –4.46 to –0.29; I 2 = 98%: low certainty), with most evidence reflecting systemic and peripheral PWV. Changes in arterial stiffness did not differ from those observed after land-based exercise (6 studies; SMD = –0.07, 95% CI: –0.34 to 0.20; I 2 = 0%, moderate certainty). For endothelial function, aquatic exercise may improve outcomes versus non-exercise controls (6 studies; SMD = 0.91, 95% CI: 0.39 to 1.43; I 2 = 68%; low certainty) and may lead to greater improvements than land-based exercise (7 studies; SMD = 0.55, 95% CI: 0.05 to 1.06; I 2 = 75%; low certainty). Conclusion Aquatic exercise improves systemic and peripheral arterial stiffness as well as endothelial function compared with non-exercising controls. Changes in arterial stiffness do not differ from those observed after land-based exercise. Aquatic exercise may provide greater improvement in endothelial function than land-based exercise, though this is supported by low-certainty evidence, and substantial heterogeneity limits confidence in the generalizability of this finding. PROSPERO registration CRD42025642087.